RGD-conjugated two-photon absorbing near-IR emitting fluorescent probes for tumor vasculature imaging. Issue 43 (9th September 2015) - Yue, Xiling; Morales, Alma R.; Githaiga, Grace W.; Woodward, Adam W.; Tang, Simon; Sawada, Junko; Komatsu, Masanobu; Liu, Xuan; Belfield, Kevin D.
Abstract : Novel two-photon absorbing fluorescent probes were conjugated with an integrin-targeting peptide, resulting in enhanced tumor vasculature imaging. Abstract : Observation of the activation and inhibition of angiogenesis processes is important in the progression of cancer. Application of targeting peptides, such as a small peptide that contains adjacentl -arginine (R), glycine (G) andl -aspartic acid (D) residues can afford high selectivity and deep penetration in vessel imaging. To facilitate deep tissue vasculature imaging, probes that can be excited via two-photon absorption (2PA) in the near-infrared (NIR) and subsequently emit in the NIR are essential. In this study, the enhancement of tissue image quality with RGD conjugates was investigated with new NIR-emitting pyranyl fluorophore derivatives in two-photon fluorescence microscopy. Linear and nonlinear photophysical properties of the new probes were comprehensively characterized; significantly the probes exhibited good 2PA over a broad spectral range from 700–1100 nm. Cell and tissue images were then acquired and examined, revealing deep penetration and high contrast with the new pyranyl RGD-conjugates up to 350 μm in tumor tissue.